2014
DOI: 10.1063/1.4893473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aluminum oxide tunnel barriers by combining transport measurements and transmission electron microscopy imaging

Abstract: We present two approaches for studying the uniformity of a tunnel barrier. The first approach is based on measuring single-electron and two-electron tunneling in a hybrid single-electron transistor. Our measurements indicate that the effective area of a conduction channel is about one order of magnitude larger than predicted by theoretical calculations. With the second method, transmission electron microscopy, we demonstrate that variations in the barrier thickness are a plausible explanation for the larger ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
(33 reference statements)
0
26
1
Order By: Relevance
“…This distribution (black bars in Fig. 6) does not follow a Gaussian distribution unlike the results of the two recent studies, 30,31 which performed cross-section HRTEM analysis of thermally grown AlO x tunnel barrier. We believe that the reason for this dissimilarity is that the mentioned studies 30,31 analyzed the thickness distribution of great number of points in their samples, and also, the type of junctions was different (Al/AlO x /Al 30 and Cu/AlO x /Al 31 ) from our junctions.…”
Section: B Hrtem Analysis and The Tunnel Barrier Modelcontrasting
confidence: 47%
“…This distribution (black bars in Fig. 6) does not follow a Gaussian distribution unlike the results of the two recent studies, 30,31 which performed cross-section HRTEM analysis of thermally grown AlO x tunnel barrier. We believe that the reason for this dissimilarity is that the mentioned studies 30,31 analyzed the thickness distribution of great number of points in their samples, and also, the type of junctions was different (Al/AlO x /Al 30 and Cu/AlO x /Al 31 ) from our junctions.…”
Section: B Hrtem Analysis and The Tunnel Barrier Modelcontrasting
confidence: 47%
“…7. We do not have direct evidence what causes this increase, but point out that transmission electron microscopy results on annealing of magnetic tunnel junctions with AlOx barriers 42 have shown homogenization of the tunneling barrier, which could explain the increase as the thinnest barrier regions dominating conductance 40,43 are removed. For a number of both Al-AlO x -Al and Al:Mn-AlO x -Al junctions, we also studied the stabilization properties of the junctions after annealing, for some junctions for over five years, with some representative data shown in Fig.…”
Section: Annealing Treatment and Agingmentioning
confidence: 95%
“…It was also shown that for typical non-annealed junctions, the barrier fluctuations can increase the Andreev current by a large factor ∼ 60, based on the barrier thickness variations observed with TEM imaging. 43 Thus, if the barrier becomes more uniform after annealing as has been seen in some cases, 42 strong improvements in the suppression of Andreev-current are expected. …”
Section: Electrical Characterization Of the Al:mn-alo X -Al Nis Jmentioning
confidence: 99%
See 1 more Smart Citation
“…I gso and I gdo are parasitic leakage currents through gate-to-S/D extension overlap region; and I gc is the gate-to-inverted channel tunneling current. Part of I gc is collected by the source (I gs ) while the rest goes to the drain (I gd ) [11,12]. Considering overall leakage currents, the relation between direct tunneling current and dielectric thickness is studied in detail.…”
Section: Ln( )mentioning
confidence: 99%